Coloniality, (Black) Theology and Liberation: Reflections on John Chilembwe - Jong, Thandi Soko-de (My University, 2022)
This paper focuses on the influence of Black Liberation theology on the development work of the Providence Industrial Mission (PIM) in colonial times. It draws from previous research as well as new developments like the growing public interest in Chilembwe such as we saw in July 2021 when it was announced that the “Antelope”, a sculptural restaging of a photograph of Chilembwe and a British missionary in which the artist “elevated Chilembwe and his story, revealing the hidden narratives of underrepresented people in the history of the British Empire in Africa and beyond.” Among the narratives that I would like to reflect on in this paper is the less spoken about link between Chilembwe’s theology and that of what we can term “early forms” of Black theology. In the context of this paper, I argue that early forms of Black theology influenced Chilembwe’s struggle against colonisation in the country now known as Malawi.
Keywords: Black Theology; John Chilembwe; Malawi; Liberation; Colonisation